Dispersing transition metal vacancies in layered double hydroxides by ionic reductive complexation extraction for efficient water oxidation. Issue 36 (30th July 2019) - Xie, Yang-Shan; Wang, Zheng; Ju, Min; Long, Xia; Yang, Shihe
Abstract : NiCu LDH with atomic vacancies created via a facile IRCE method shows advanced electrocatalytic performance towards water oxidation. Abstract : Creating atomic defects in nanomaterials is an effective approach to promote the catalytic performance of a catalyst, but the defective catalysts are often prone to mechanical collapse if not properly synthesized. The uncontrollably formed defects also make it difficult to systematically investigate their effects on the catalytic performance. Herein, we report an efficient method of ionic reductive complexation extraction (IRCE) to fabricate atomic vacancies in a transition metal based nanomaterial without damaging its nanostructure, turning the otherwise catalytically inactive material to an advanced catalyst towards water oxidation in alkaline electrolyte. Here nickel based layered double hydroxide mixed with Cu(ii ) is used to demonstrate the concept. With a tunable content and uniform dispersion of Cu(ii ) on the brucite layer of the LDH, a suitable complexing agent could specifically combine with and remove the target Cu(ii ), thereby creating the desired vacancies. The resulting vacancy rich TM LDH is found to be an excellent OER electrocatalyst with a low overpotential and small Tafel slope, due to the purposely modulated geometric and electronic structures of the active sites, and the greatly decreased charge transfer resistance.